RETRIEVAL OPERATORS OF REMOTE SENSING APPLICATIONS - Ahmad, T.; Shah, A. (The Nucleus, 2014)
A set of operators of remote sensing applications have been proposed to fulfill most of the Functional Requirements (FR). These operators capture the functions of the applications, which can be considered as the services provided by the applications. In general, a good application meets maximum FR from user. In this paper, we have defined a remote sensing application by a set, having all images created at dissimilar time instances, and each image is categorized into set of different layers.